x(m+2)+y(m-2)=z(m-7)

Simple and best practice solution for x(m+2)+y(m-2)=z(m-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(m+2)+y(m-2)=z(m-7) equation:


Simplifying
x(m + 2) + y(m + -2) = z(m + -7)

Reorder the terms:
x(2 + m) + y(m + -2) = z(m + -7)
(2 * x + m * x) + y(m + -2) = z(m + -7)

Reorder the terms:
(mx + 2x) + y(m + -2) = z(m + -7)
(mx + 2x) + y(m + -2) = z(m + -7)

Reorder the terms:
mx + 2x + y(-2 + m) = z(m + -7)
mx + 2x + (-2 * y + m * y) = z(m + -7)

Reorder the terms:
mx + 2x + (my + -2y) = z(m + -7)
mx + 2x + (my + -2y) = z(m + -7)

Reorder the terms:
mx + my + 2x + -2y = z(m + -7)

Reorder the terms:
mx + my + 2x + -2y = z(-7 + m)
mx + my + 2x + -2y = (-7 * z + m * z)

Reorder the terms:
mx + my + 2x + -2y = (mz + -7z)
mx + my + 2x + -2y = (mz + -7z)

Solving
mx + my + 2x + -2y = mz + -7z

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1mz' to each side of the equation.
mx + my + 2x + -1mz + -2y = mz + -1mz + -7z

Reorder the terms:
mx + my + -1mz + 2x + -2y = mz + -1mz + -7z

Combine like terms: mz + -1mz = 0
mx + my + -1mz + 2x + -2y = 0 + -7z
mx + my + -1mz + 2x + -2y = -7z

Add '-2x' to each side of the equation.
mx + my + -1mz + 2x + -2x + -2y = -2x + -7z

Combine like terms: 2x + -2x = 0
mx + my + -1mz + 0 + -2y = -2x + -7z
mx + my + -1mz + -2y = -2x + -7z

Add '2y' to each side of the equation.
mx + my + -1mz + -2y + 2y = -2x + 2y + -7z

Combine like terms: -2y + 2y = 0
mx + my + -1mz + 0 = -2x + 2y + -7z
mx + my + -1mz = -2x + 2y + -7z

Reorder the terms:
mx + my + -1mz + 2x + -2y + 7z = -2x + 2x + 2y + -2y + -7z + 7z

Combine like terms: -2x + 2x = 0
mx + my + -1mz + 2x + -2y + 7z = 0 + 2y + -2y + -7z + 7z
mx + my + -1mz + 2x + -2y + 7z = 2y + -2y + -7z + 7z

Combine like terms: 2y + -2y = 0
mx + my + -1mz + 2x + -2y + 7z = 0 + -7z + 7z
mx + my + -1mz + 2x + -2y + 7z = -7z + 7z

Combine like terms: -7z + 7z = 0
mx + my + -1mz + 2x + -2y + 7z = 0

The solution to this equation could not be determined.

See similar equations:

| 8x+6y+4z=6 | | -4x-3y=25 | | 64.5g=-25.8 | | -4/7-5/3v=-1/3 | | 0.30(x+100)+0.50x=46 | | 8x^2+3x+5=0 | | 5.50(75+x)=1100 | | |x-3|+2=2 | | 15/125 | | -3/8z=-12 | | 3t+1/7=t+4/14+t-2/14 | | 8x+8y+5z=1 | | |x-1|=0 | | 2x+12/7=3x-1 | | (-x^2)-12=0 | | t=r+k/4(w) | | 8(-5+4m)= | | 5w^2+19w-1=0 | | 7((x+4)/7)-4 | | 5w^2+19w-1=o | | .20x+50=.30x | | t=r+k/4*w | | x-60+y=1362 | | |6x|=18 | | 2x+5y+7z=14 | | X-27=12 | | x-602+y=136 | | 7((x+4)/7) | | 2s-25=-17+6s | | 2x/2-x=x/10-21/2 | | |x+2|-3=9 | | (k-7)2=42 |

Equations solver categories